The role of repetitive DNA in structure and evolution of sex chromosomes in plants - Kejnovsky, E; Hobza, R; Cermak, T; Kubat, Z; Vyskot, B (Heredity, 2009)
Eukaryotic genomes contain a large proportion of repetitive DNA sequences, mostly transposable elements (TEs) and tandem repeats. These repetitive sequences often colonize specific chromosomal (Y or W chromosomes, B chromosomes) or subchromosomal (telomeres, centromeres) niches. Sex chromosomes, especially non-recombining regions of the Y chromosome, are subject to different evolutionary forces compared with autosomes. In non-recombining regions of the Y chromosome repetitive DNA sequences are accumulated, representing a dominant and early process forming the Y chromosome, probably before genes start to degenerate. Here we review the occurrence and role of repetitive DNA in Y chromosome evolution in various species with a focus on dioecious plants. We also discuss the potential link between recombination and transposition in shaping genomes.
Keywords: rostliny; Plants; Repetitive Sequences, Nucleic Acid; repetitivní sekvence nukleových kyselin; Sex Chromosomes; molekulární evoluce; pohlavní chromozomy; Evolution, Molecular; chromozomy rostlin; Chromosomes, Plant